Analisis Yuridis Terhadap Pengaturan Liquid Pods Dalam Perspektif Penyalahgunaan Zat Psikotropika di Indonesia (Studi Putusan Nomor 817/Pid.Sus/2025/Pn Kis) - Mangaraja Manurung; Rizky Akhbar Barus (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Technological developments have encouraged innovation in the electronic cigarette industry, including the emergence of liquid pods used in pod-based vaping devices. In practice, liquid pods are not only utilized as a medium for nicotine consumption but are also increasingly misused as a means of consuming psychotropic substances and narcotics. This situation creates legal issues because Indonesian laws have not specifically regulated liquid pods as a medium for the abuse of prohibited substances. This study aims to analyze the legal regulation of liquid pods from the perspective of psychotropic substance abuse in Indonesia and to examine judicial considerations in Decision Number 817/Pid.Sus/2025/PN Kis. This research employs a normative legal research method using statutory, conceptual, and case approaches. The data were obtained through library research involving primary, secondary, and tertiary legal materials and were analyzed qualitatively. The findings indicate that legal regulations concerning liquid pods remain fragmented across several legislative instruments, creating a legal vacuum regarding their misuse. Furthermore, the judicial considerations in the examined decision demonstrate that judges considered both juridical and non-juridical aspects in determining criminal liability.